2013
DOI: 10.4049/jimmunol.1202398
|View full text |Cite
|
Sign up to set email alerts
|

IgG Antibodies in Food Allergy Influence Allergen–Antibody Complex Formation and Binding to B Cells: A Role for Complement Receptors

Abstract: Allergen–IgE complexes are more efficiently internalized and presented by B cells than allergens alone. It has been suggested that IgG Abs induced by immunotherapy inhibit these processes. Food-allergic patients have high allergen-specific IgG levels. However, the role of these Abs in complex formation and binding to B cells is unknown. To investigate this, we incubated sera of peanut- or cow’s milk–allergic patients with their major allergens to form complexes and added them to EBV-transformed or peripheral b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…It has been reported that mast cells can respond not only to IgE antibodies but also to IgG antibodies [37] . In addition IgG antibodies in food allergy may even influence allergen-IgE complex formation and bind to B cells, which is quite opposite the traditional concept that IgG antibodies are supposed to inhibit these processes [38] . Therefore IgG antibodies probably serve as mediation effects rather than inhibition in hypersensitivity reaction caused by food intolerance.…”
Section: Discussionmentioning
confidence: 80%
“…It has been reported that mast cells can respond not only to IgE antibodies but also to IgG antibodies [37] . In addition IgG antibodies in food allergy may even influence allergen-IgE complex formation and bind to B cells, which is quite opposite the traditional concept that IgG antibodies are supposed to inhibit these processes [38] . Therefore IgG antibodies probably serve as mediation effects rather than inhibition in hypersensitivity reaction caused by food intolerance.…”
Section: Discussionmentioning
confidence: 80%
“…One shrimp allergic patient was not able to participate as a result of emigration. BAT's were performed as described previously by Meulenbroek et al [13] with minor modifications. Cells were incubated with a dilution series (1:10 7 to 1:10 2 ) of insect extracts (5 mg/mL).…”
Section: Basophil Activation Test (Bat)mentioning
confidence: 99%
“…IgG4-producing cells can undergo secondary class switch to IgE (31), as was shown also for IgG1 in mice (32); thus, a fraction of the IgE repertoire may reflect a subset of the IgG4 repertoire in humans. Although IgG4 seems to mediate tolerance during successful treatment in allergic patients, its function during allergen-Ab complex formation in food allergies is unknown (33). Moreover, IgG4 can also mediate autoimmunity (e.g., pemphigus vulgaris) and might play a pathogenic role in newly identified "IgG4-related disease" (34).…”
mentioning
confidence: 99%